The economics of industrial subsidies - Whiting, Alan (London Her Majesty's Stationery Office, 1975)
The papers in this volume were presented at a conference on the economics of industrial subsidies which was held at the Civil Service College, Sunningdale, in February 1975
Includes bibliography
osc 21/10/2019
Loans
Keywords: Economics; Subsidies; Industries; Great Britain